CANCER ON TIKTOK–EVALUATING POSITIVE CULTURE AND ONLINE SELF-DISCLOSURE USING DIRECTED CONTENT ANALYSIS AND IN-DEPTH INTERVIEWS - Pluta, Magdalena; Siuda, Piotr (AoIR Selected Papers of Internet Research, 2023)
The presented paper characterizes TikTok practices of users with cancer and uses notions of social media as positive culture (presenting oneself without undesirable traits) and online self-disclosure understood as providing intimate, private information about oneself. The research continues the work on self-disclosure of women with breast cancer using Instagram. However, this previous research revolved around posts, and thus was limited. The current study on TikTok asks the following questions: 1) are TikTok videos disclosing information in the manner the previous research on Instagram shows? 2) What are the creators’ motivations and what meanings do they give to disclosing cancer and how do the users position themselves considering the positive culture? The study uses categories from previous work and combines qualitative directed content analysis (DCA; 862 videos are analyzed) with in-depth interviews (n=8), and these go beyond DCA to a more nuanced understanding of the users’ lived experience. Similar to Instagram, TikTok is a tool for negative (e.g., fears, anxiety, pain) and positive self-disclosure (e.g., joyful life events, self-acceptance, self-afﬁrmation) with the prevalence of positive and educational videos (e.g. prevention, debunking stereotypes and normalizing the disease). The respondents feel especially competent to educate others because of their experiences. The research undermines the traditional understanding of online self-disclosure, as for users seeking support is not that important, compared to informing and warning others. Also, the study debunks positive culture as a too-general category, as the interviewees constitute a particular niche and seem not to care how they are perceived while disclosing cancer.